EKSPLORASI PENERAPAN AJAX PADA FRAMEWORK CAKEPHP UNTUK MENDUKUNG PROSES BISNIS DI ONLINE SHOP - Raden Putri Pratiwi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to find out and understand the application of AJAX on the Cake PHPFramework and can apply it in the ordering process at online shops / online shops.Customers can view information and place orders on this application easily. In thispaper, the researcher uses the method of literature study, exploration andapplication development. This research produces exploratory results that can bestudied by readers and can apply the results of these explorations to the case study